Prediabetes, diabetes, and other CVD-related conditions among Asian populations in Los Angeles County, 2014. Issue 7 (3rd October 2019) - Zheng, Guili; Family, Leila; Hsu, Shelly; Rivera, Jennifer; Mondy, Cristin; Cloud, Jennifer; Frye, Douglas; Smith, Lisa V.; Kuo, Tony
ABSTRACT: Objective: To assess the prevalence of four common health conditions related to cardiovascular disease risk among Asians in Los Angeles County. Methods: A survey of Asians in Los Angeles County was conducted utilizing purposive sampling to recruit from the region's Service Planning Areas 3 and 4; these underserved areas contain high density of Asian populations. Descriptive and multivariable regression analyses were performed to explore and describe potential associations between self-reported diagnoses of prediabetes, diabetes, hypertension, and high cholesterol and body mass index (measured with non-Asian versus Asian cut points) by race/ethnicity (Chinese/Filipino/Korean/Taiwanese/Thai/Vietnamese). Results: The survey response rate was nearly 60%. The analysis included 1, 377 Asians, self-identified as either Chinese ( n  = 700), Filipino ( n  = 69), Korean ( n  = 339), Taiwanese ( n  = 48), Thai ( n  = 115), or Vietnamese ( n  = 106). Results showed that, in comparison to other Asians, Filipinos had the highest risks for two of the four conditions described. Other results by subgroup affirmed a similar heterogeneous pattern of Asian health locally. Conclusions: These and other results from the survey point to potential gaps in healthcare needs of Asians, and to opportunities where local public health efforts could help increase these populations' access to cardiovascular disease-related health and social services.